2011
DOI: 10.1017/s002237781100050x
|View full text |Cite
|
Sign up to set email alerts
|

Dust ion-acoustic solitary structures in non-thermal dusty plasma

Abstract: Dust ion-acoustic solitary structures have been investigated in an unmagnetized non-thermal plasma consisting of negatively charged dust grains, adiabatic positive ions, and non-thermal electrons. Whenever the non-thermal parameter exceeds a critical value, the present system supports negative potential double layer solution. However, this double layer solution is unable to restrict the occurrence of negative potential solitary waves of the present system. As a result, the occurrence of one type of negative po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…Since the description of solitary waves is usually given in terms of the electrostatic potential, not of the associated electric field, pseudopotentials with three local extrema were encountered earlier [9][10][11][12] but not recognized as differing from ordinary solitons.…”
Section: Introductionmentioning
confidence: 99%
“…Since the description of solitary waves is usually given in terms of the electrostatic potential, not of the associated electric field, pseudopotentials with three local extrema were encountered earlier [9][10][11][12] but not recognized as differing from ordinary solitons.…”
Section: Introductionmentioning
confidence: 99%
“…Shukla and Silin (1992) were the first to report theoretically the existence of dust-ionacoustic (DIA) waves. Nonlinear waves associated with DIA waves, particularly the DIA solitary waves (SWs) (Moslem et al 2005;Alinejad 2010;Alinejad 2011a, b;El-Taibany et al 2011;Rahman and Mamun 2011;Das et al 2012;El-Labany et al 2012a;Yasmin et al 2012b) and dust ion-acoustic shock waves (DIASHWs) (Luo et al 1999;Nakamura et al 1999;Popel et al 2000;Nakamura and Sharma 2001;Mamun and Shukla 2002;Shukla and Mamun 2003;Eliasson and Shukla 2005; Alinejad 2010; Mamun and Tasnim 2010;El-Labany et al 2012b), have received a baronial interest in space and laboratory dusty plasmas. The theoretical prediction of Shukla and Silin (1992) has been conclusively verified by a number of laboratory experiments (Barkan et al 1996;Nakamura et al 1999;Merlino and Goree 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Supersolitons have typical characteristics, some of which, remarkably, were already present in earlier papers (White et al 1972;Verheest 2009;Baluku et al 2010;Verheest 2011;Das et al 2012), but were not recognized as being special. Although White et al (1972) clearly indicated that an additional soliton range can exist, separated from the standard range by a discontinuous jump in amplitude, there seems to have been no further exploration of this, mainly because the electric field signatures were not investigated, and their wiggles are not seen.…”
Section: Introductionmentioning
confidence: 92%